2014
DOI: 10.1097/aap.0000000000000127
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Hematoma Formation in Patients With Continuous Femoral Catheters Following Total Knee Arthroplasty While Receiving Rivaroxaban as Thromboprophylaxis

Abstract: In this prospective observational study, the concurrent administration of continuous femoral nerve block, the once-daily administration of the anticoagulant rivaroxaban, and the timed removal of the femoral catheter were not associated with hematoma formation resulting in neurovascular compromise at the femoral catheter insertion site or groin area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 10 publications
(4 reference statements)
3
12
0
Order By: Relevance
“…5 As there is no suggestion that factor Xa inhibitors can be taken safely in patients with neuraxial catheters, it is implied that patients with peripheral nerve catheters would be at similar risk for bleeding. Similar to Idestrup et al, 6 we observed no hematoma formation in patients receiving factor Xa inhibitors after adductor canal catheter removal. In light of our small series and previously published literature, updated guidelines for postoperative analgesia strategies could consider maintenance and removal of a peripheral nerve catheter in the setting of anticoagulation with a factor Xa inhibitor, especially if the catheter is placed at a site than can be physically compressed should bleeding become evident.…”
Section: Incidence Of Clinicallysupporting
confidence: 90%
See 1 more Smart Citation
“…5 As there is no suggestion that factor Xa inhibitors can be taken safely in patients with neuraxial catheters, it is implied that patients with peripheral nerve catheters would be at similar risk for bleeding. Similar to Idestrup et al, 6 we observed no hematoma formation in patients receiving factor Xa inhibitors after adductor canal catheter removal. In light of our small series and previously published literature, updated guidelines for postoperative analgesia strategies could consider maintenance and removal of a peripheral nerve catheter in the setting of anticoagulation with a factor Xa inhibitor, especially if the catheter is placed at a site than can be physically compressed should bleeding become evident.…”
Section: Incidence Of Clinicallysupporting
confidence: 90%
“…4 Although intravenous anesthesia can substitute for volatile agents in many clinical scenarios, there is rising evidence that our intravenous drugs are also accumulating in soil, ground water, and thus also in drinking water. 6 Based on the Stockholm County Council classification of hazardous potential drugs, propofol, for example, has the maximum rating in all 3 measured categories of persistence, bioaccumulation, and toxicity. 7 The most "green" anesthetic is one not given in the form of an inhalational or an intravenous agent.…”
Section: Incidence Of Clinicallymentioning
confidence: 99%
“…The risk of bleeding associated with thromboprophylaxis following joint replacement varies according to the study and the drug. Recently, Idestrup et al reported on the combination of rivaroxaban for thromboprophylaxis initiated at 10 am on POD 1 following a total replacement in patient and the placement of a continuous femoral nerve block prior to surgery . According to the authors' study protocol, the perineural catheter was removed after a free anticoagulation interval of 20 hours on POD 2 and the next dose of rivaroxaban was administered 4 hours after.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of nerve blocks, the risk of major bleeding including retroperitoneal hematoma following the administration of rivaroxaban has been estimated to be between 0.001 and 0.7% . However, the relative risk of bleeding from the combination of rivaroxaban and peripheral nerve blocks was undocumented until Idestrup et al assessed the risk of bleeding in patients receiving continuous femoral blocks and rivaroxaban for thromboprophylaxis . Although they concluded that the combination was safe, the study did not document the relative risk of combining rivaroxaban with deep and plexus nerve blocks or the frequency of other bleeding events associated with the administration of rivaroxaban.…”
Section: Introductionmentioning
confidence: 99%
“…2 Dr Chelly notes that we reported our discovered rates of local oozing and development of a palpable mass, stating that this is likely due to local tissue trauma as opposed to the combination of the continuous femoral nerve block and the use of rivaroxaban. We have similarly noted local tissue trauma as a risk factor with regard to oozing and possible hematoma formation for our patients as discussed in our article.…”
Section: Reply To Dr Chellymentioning
confidence: 90%